Wood ant assemblages of Formica rufa group on lake islands and in mainland woodland in Central Finland - Sorvari, Jouni (Entomologica Fennica, 2018)
Associations of island size and isolation on the occurrence and species richness of five wood ant species of the Formica rufa group (F. rufa, F. aquilonia, F. lugubris, F. polyctena and F. pratensis) was tested in the Lake Konnevesi archipelago in Central Finland. In addition, the species composition was compared to that of mainland forests of the same region. Island isolation had no associations with the wood ant occurrence in this archipelago, but for most species, increasing island size was positively associated with the occurrence probability. According to the findings among the five species, Formica lugubris is the best adapted for insular living. There was a positive species–area relationship as the species richness of wood ants increased with an increasing island size. The island community of wood ants was dominated by colonies of the monogynous (single queen) species whereas the mainland community was dominated by those of polygynous (multiple queen) species.